Sustainable value propositions of a new technology for targeted nitrogen regulation. (20th February 2022) - Nygaard, Kenneth; Schaper, Stefan; Jacobsen, Brian H.; Hansen, Birgitte
Abstract: Nitrogen (N) provides the agriculture industry with a wicked problem: it is an essential nutrient for efficient crop production, but N losses from agricultural production can harm both the stability of the environment and the health of humans. To limit this, targeted N regulation at the ID15 (1500 ha) level is slowly becoming a reality for farmers and authorities in Denmark. This paper explores the formulation of value propositions connected to developed technologies and concepts for retention mapping at the field level for more detailed targeted regulation. We explore all this through a comprehensive longitudinal ethnographic case study over a period of three years. We use the value proposition canvas to make sense of the viewpoints of the involved stakeholder groups. Our empirical setting is a large-scale research project in Denmark, a country that has high environmental goals regarding nitrogen loading. The publicly funded project involved a multitude of stakeholders, ranging from industry consultants, regulators, farmers and researchers from several disciplines. Important for our study is the fact that much of Denmark's regulation is based on a consensus-driven approach. Thus, it provides a compelling setting for exploring the creation of value propositions through multisector stakeholder engagement. Our findings indicate that, while there is a general movement towards targeted N regulation due to an advancement of knowledge, the practical side of its implementation is less straightforward. Here, stakeholder-formulated value propositions can facilitate this process, not only being connected to the measurement technology, but also relying on a link to a regulatory transformation. Graphical abstract: Image 1 Highlights: Value propositions for new technologies and concepts for detailed nitrogen retention maps of the subsurface. Cleaner and more sustainable agricultural production and water management. Manifold complications connected to the implementation of targeted nitrogen regulation in agriculture. Stakeholder engagement essential for articulating relevant value propositions. Important steps towards a new governance model for targeted nitrogen regulation.